THE APPLICATION OF MARKOV CHAIN MODEL TO CALCULATE PREMIUM AND RESERVE OF ENDOWMENT INSURANCE - Haryanto, Dwi (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
The calculation of premiums and reserves are two essential parts of insurance. The calculation of premiums and reserves in life insurance involves using mortality tables. This research constructed a mortality table for 20-year endowment insurance using the Markov chain model. Two reasons make the policy inactive, namely death or withdrawal. The initial age used in this research is 30 years. Meanwhile, the maximum age to join this life insurance is 40 years. The mortality table that has been obtained is used to calculate premiums and reserves. Furthermore, from the research done, it was found that the age of entry to become a member of endowment insurance affects the number of premiums that must be paid. Meanwhile, the number of reserves required will increase with the increase of customers and the period of calculation of reserves